2016
DOI: 10.1021/acscentsci.6b00014
|View full text |Cite
|
Sign up to set email alerts
|

Crowding and Anomalous Capacitance at an Electrode–Ionic Liquid Interface Observed Using Operando X-ray Scattering

Abstract: Room temperature ionic liquids are widely recognized as novel electrolytes with properties very different from those of aqueous solutions, and thus with many potential applications, but observing how they actually behave at electrolytic interfaces has proved to be challenging. We have studied the voltage-dependent structure of [TDTHP]+[NTF2]− near its interface with an electrode, using in situ synchrotron X-ray reflectivity. An anion-rich layer develops at the interface above a threshold voltage of +1.75 V, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 49 publications
7
58
0
Order By: Relevance
“…It means that counterions accumulate in more than one layer close to the charged surface because this charge is very high and because the bulky counter-ions cannot compensate this charge with one dense layer of pure counter-ions. Crowding was observed experimentally by an X-ray reflectivity study 47 in an ionic liquid containing bistriflimide (TFSI) starting from a surface charge density of ∼ 50µC/cm 2 which is in agreement with the simulated value for overscreening leading to a multilayer structure or crowding. Additional counter-ions different from the one of the ionic liquid are considered as they are present in our experiments (they are the initial counter-ions of the particles, localised close to the nanoparticle surface in the ionic liquid).…”
Section: Nanoscale Advances Accepted Manuscriptsupporting
confidence: 79%
“…It means that counterions accumulate in more than one layer close to the charged surface because this charge is very high and because the bulky counter-ions cannot compensate this charge with one dense layer of pure counter-ions. Crowding was observed experimentally by an X-ray reflectivity study 47 in an ionic liquid containing bistriflimide (TFSI) starting from a surface charge density of ∼ 50µC/cm 2 which is in agreement with the simulated value for overscreening leading to a multilayer structure or crowding. Additional counter-ions different from the one of the ionic liquid are considered as they are present in our experiments (they are the initial counter-ions of the particles, localised close to the nanoparticle surface in the ionic liquid).…”
Section: Nanoscale Advances Accepted Manuscriptsupporting
confidence: 79%
“…In order to better utilize ionic liquids in electrochemical energy storage and conversion systems, researchers have been trying to obtain a deeper understanding of their dynamics and interactions with solid interfaces using various techniques. For instance, one can probe out‐of‐plane ionic ordering near the liquid/solid interface using atomic force microscopy (AFM) or X‐ray reflectivity . Several low‐temperature scanning tunneling microscopy studies on in‐plane ordering have also been reported for a low coverage of ionic liquids deposited on gold and silver surfaces .…”
mentioning
confidence: 99%
“…Recent work suggests that the electrode surface is overcrowded with layers of ions causing a significant increase in the capacitance. 135 The capacitance minimum location as a function of AC frequency is shown in Figure 3.1.7c. There is a change in the capacitance minimum location from ~100 mV vs. Fc/Fc + for the 9 Hz data to ~50 mV vs. Fc/Fc + at higher frequencies.…”
Section: Role Of Watermentioning
confidence: 99%